American Ballet Theatre's online dictionary
American Ballet Theatre's online dictionary Dover Publications has graciously allowed to use 170 terms from the Technical Manual and Dictionary of Classical Ballet. We took those definitions to our dancers and said, "Show us how it is supposed to be done." The purpose of this project is to bring dance to the Web -- to make it accessible to everyone. As you view this section, keep that goal in mind because a great number of concessions had to be made to make this possible.